2015
DOI: 10.3758/s13423-015-0970-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the contribution of target repetition and target expectation to the emergence of the prevalence effect in visual search

Abstract: Behavior in visual search tasks is influenced by the proportion of trials on which a target is presented (the target prevalence). Previous research has shown that when target prevalence is low (2 % prevalence), participants tend to miss targets, as compared with higher prevalence levels (e.g., 50 % prevalence). There is an ongoing debate regarding the relative contributions of target repetition and the expectation that a target will occur in the emergence of prevalence effects. In order to disentangle these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…This has been seen in blue jays who will pass over less common prey while foraging for the more common (Bond & Kamil, 2002). Similar effects are seen in search when one target type is rarer than another (Godwin et al, 2015; Hout, Walenchok, Goldinger, & Wolfe, 2015). …”
Section: Resultssupporting
confidence: 52%
“…This has been seen in blue jays who will pass over less common prey while foraging for the more common (Bond & Kamil, 2002). Similar effects are seen in search when one target type is rarer than another (Godwin et al, 2015; Hout, Walenchok, Goldinger, & Wolfe, 2015). …”
Section: Resultssupporting
confidence: 52%
“…Second, our results can also help to offer new insights into how participants fail to detect targets in visual search. It has been noted that targets are often missed as a consequence of failures of perceptual identification (Cain et al., ; Schwark et al., )—that is, even after fixating the target object, the target is still missed by participants (Engel, ; Godwin et al., ,a,b; Godwin et al., ; Gould & Cairn, ; Hooge & Erkelens, ; Hout, Walenchok, Goldinger, & Wolfe, ; Nodine & Kundel, ). These failures have important societal consequences, such as in radiographic image screening, where tumors can go undetected and missed by searchers.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of perceptual identification errors has been used as evidence against strict direct‐control accounts, with such occurrences being regarded as a natural by‐product of the fact that fixations can be terminated by an indirect mechanism (e.g., an autonomous timer) that drives fixations to new locations irrespective of whether or not the processing of an object at a given fixation location has been completed. However, more recent studies (Godwin, Menneer, Riggs, Cave, & Donnelly, ; Godwin et al., ; Hout et al., ) have found that perceptual identification errors are more likely to occur when the target is presented on a small proportion of trials (5% of trials) compared with a higher proportion of trials (45%), perhaps because of priming from target repetition and/or expectations about the likelihood of a target being presented (Godwin et al., ,b). This finding suggests that failures to detect the target upon fixating it may reflect object identification failures rather than being a consequence of some indirect mechanism, as predicted by indirect‐control accounts.…”
Section: A New Approach: Using Lag‐2 Revisits To Understand Trade‐offmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a reduction in target prevalence increases failures of perceptual selection, whereby searchers fixate fewer objects in each trial as prevalence is reduced [48]. It is worth noting that efforts to overcome this shortcoming by providing feedback in relation to where fixations have and have not been made are unlikely to help [49,50].…”
Section: The Problem Of Low Prevalencementioning
confidence: 99%